Design of Load Path-oriented BCCz Lattice Sandwich Structures - Zhao, Shengjie; Zong, Xinxiang; Wu, Nan (Journal of physics. Conference series, 2022)
Lattice structures are increasingly used in lightweight designs due to the advances of additive manufacturing. The overall performance of the lattice structures highly depends on the lattice cell arrangement. Previous studies show that body-centered cubic with z-axis reinforcement (BCCz) lattice has higher stiffness and strength compared to regular body-centered cubic (BCC) lattice subject to unidirectional compression. In this report, a load path-based methodology for the design of BCCz lattice sandwich structure with variable reinforcement directions is presented. A homogenization model of the sandwich structure with a specified volume fraction is developed first. Load path analysis is then conducted on the homogenization model to calculate the pointing stress vectors, which are lastly used to determine the orientations of BCCz cells. Based on the numerical simulations of a cantilever sandwich structure, the proposed lattice design has superior specific stiffness over the designs based on BCC or uniformly oriented BCCz unit cells.